PENGARUH PERPUSTAKAAN DIGITAL TERHADAP MINAT BACA SISWA MAN 1 KUANTAN SINGINGI - Zulpines Indira Putri; Gimin Gimin; Supentri Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was based on the results of observations made at MAN 1 Kuantan Singingi that the dominant students at MAN 1 Kuantan Singingi still had a low interest in reading. This can be seen from the fact that most students only visit and read books in the library when they are assigned by the teacher, not because of their own wishes. The formulation of the problem in this research is whether there is an influence of digital libraries on students' reading interest at MAN 1 Kuantan Singingi. The population in this study were all MAN 1 Kuantan Singingi students, totaling 618 students and the sample taken in this study was 20% of the total population, namely 124 respondents consisting of classes X, XI, XII using the Proportionate Stratified Random Sampling Technique. The data collection methods used in this research are observation, questionnaires and documentation. Data processing using statistical analysis using a simple linear regression formula, namely obtained F count > F table, namely 71.975 > 3.92, thus Ho is rejected and Ha is accepted, which means that variable (Digital Library) on variable Y Students' Reading Interest is 37.1%.